Agricultural Land Pawning as a Social Institution in Wono Agung Village Tulang Bawang District - Raswanto, Raswanto; Sumarja, FX; Yuniati, Ati (Fakultas Hukum Universitas Lampung, 2024)
Agricultural land pawning, as outlined in Law No. 56/1960 on the Determination of Agricultural Land Area, is characterized as a collateral transaction where agricultural land is mortgaged or pledged. Social institutions can play a key role in this process, acting as facilitators for loan provisions against land collateral and helping to evaluate and understand the motivations behind agricultural land pawning. This research adopts an empirical normative approach to assess the practice. The findings reveal that agricultural land pawning in Wono Agung Village is conducted in two principal manners: verbally and in writing, aligning with the stipulations of Article 7 of Law Number 5 of 1960. The residents of Wono Agung Village typically engage in pawning their agricultural land for several reasons, including the need for capital, education expenses, expansion of agricultural land, general economic difficulties, and other urgent necessities. Challenges in the implementation of agricultural land pawning arise from issues involving both the pawn recipients and the landowners. Despite these obstacles, agricultural land pawning functions effectively as a social institution, offering a viable solution to the economic struggles faced by the villagers. These social institutions play a pivotal role in enhancing the welfare and economic conditions of the agricultural community in Wono Agung Village.